Outcomes of transitional care programs on adolescent chronic inflammatory systemic diseases: systematic review and meta-analyses - Fernando García-Rodríguez; Karina Raygoza-Cortez; Lesli Moreno-Hernandez; Rodrigo García-Pérez; Leticia Elizabeth Garza Lopez; Ana Cecilia Arana-Guajardo; Joel Omar Jáquez-Quintana; Ana Victoria Villarreal-Treviño; Manuel Enrique de la O-Cavazos; Nadina Rubio-Pérez (BMC, 2022)
Abstract Background Patients with juvenile chronic inflammatory systemic diseases (jCID) are vulnerable to many circumstances when transitioning to adult-centered healthcare; this increases the burden of disease and worsen their quality of life. Methods MEDLINE, Embase, Web of Science and Scopus were searched from inception to March 16th, 2021. We included observational, randomized controlled trials and quasi-experimental studies that evaluated a transitional care program for adolescents and young adults with jCIDs. We extracted information regarding health-related quality of life, disease activity, drop-out rates, clinical attendance rates, hospital admission rates, disease-related knowledge, surgeries performed, drug toxicity and satisfaction rates. Results Fifteen studies met our inclusion criteria. The implementation of transition programs showed a reduction on hospital admission rates for those with transition program (OR 0.28; 95% CI 0.13 to 0.61; I 2 = 0%; p = 0.97), rates of surgeries performed (OR 0.26; 95% CI 0.12 to 0.59; I 2 = 0%; p = 0.50) and drop-out rates from the adult clinic (OR 0.23; 95% CI 0.12 to 0.46; I 2 = 0%; p = 0.88). No differences were found in other outcomes. Conclusion The available body of evidence supports the implementation of transition programs as it could be a determining factor to prevent hospital admission rates, surgeries needed and adult clinic attendance rates.